2016
DOI: 10.1253/circj.cj-16-0329
|View full text |Cite
|
Sign up to set email alerts
|

Early Results of Simultaneous Transaortic Transcatheter Aortic Valve Implantation and Total Arterial Off-Pump Coronary Artery Revascularization in High-Risk Patients

Abstract: Background: Transcatheter aortic valve implantation (TAVI) has become an alternative procedure for treating aortic stenosis (AS) in patients with advanced age and severe comorbidities. Ischemic heart disease (IHD) is present with AS in 40-50% of patients with typical angina. Considering the high operative mortality and morbidity rates in these patients, hybrid TAVI and off-pump CABG (OPCAB) have become realistic treatment options. Methods and Results:Between August 2014 and November 2015, 12 patients were eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 26 publications
1
12
0
Order By: Relevance
“…Several studies described the concomitant TAVI procedure and OPCAB coronary revascularization and reported the similar 30‐day mortality as in our cohort 22,29,30 . In our study we observed 10% 30‐day mortality.…”
Section: Discussionsupporting
confidence: 86%
“…Several studies described the concomitant TAVI procedure and OPCAB coronary revascularization and reported the similar 30‐day mortality as in our cohort 22,29,30 . In our study we observed 10% 30‐day mortality.…”
Section: Discussionsupporting
confidence: 86%
“…The advantage of an upper mini-sternotomy is that pleural spaces are not open. Full sternotomy is usually performed in high-risk patients requiring combined procedures such as off-pump coronary artery bypass grafting and/or tricuspid valve repair on cardiopulmonary bypass and beating heart can be considered in selected cases ( 35 37 ). The device insertion is similar to the upper mini-sternotomy.…”
Section: Direct Transaortic Accessmentioning
confidence: 99%
“…Guidelines now tentatively recommend this combination for severe AS patients with concomitant coronary stenosis occupying > 70% of the artery diameter [2]; however not all coronary lesions are treatable with PCI. More recently, off-pump CABG (OPCAB) has been proposed as a method of complete coronary revascularisation in patients with complex stenosis and/or high SYNTAX scores [5, 6], with the off-pump technique avoiding the harmful effects of cardiopulmonary-bypass (CPB) [7]. OPCAB has been used to treat multi-vessel disease requiring a larger operative area, with a recent 4-patient series outlining its successful use immediately prior to transaortic (TAo) TAVR [8].…”
Section: Introductionmentioning
confidence: 99%
“…A modified version of OPCAB, known as minimally invasive direct CABG (MIDCAB), has been developed for the treatment of single-vessel disease, achievable through a smaller incision. Since the first documented MIDCAB plus transapical (TA) TAVR hybrid in 2010 [9], several other successful cases have been reported [5, 10]. However, only one larger study has evaluated the safety and feasibility of TAVR+OPCAB/MIDCAB to date [11], and no comparisons with TAVR+PCI and SAVR+CABG have been performed.…”
Section: Introductionmentioning
confidence: 99%